2006
DOI: 10.1002/art.22174
|View full text |Cite
|
Sign up to set email alerts
|

Large‐scale gene expression profiling reveals major pathogenetic pathways of cartilage degeneration in osteoarthritis

Abstract: Objective. Despite many research efforts in recent decades, the major pathogenetic mechanisms of osteoarthritis (OA), including gene alterations occurring during OA cartilage degeneration, are poorly understood, and there is no disease-modifying treatment approach. The present study was therefore initiated in order to identify differentially expressed disease-related genes and potential therapeutic targets.Methods. This investigation consisted of a large gene expression profiling study performed based on 78 no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

38
256
6
4

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 314 publications
(304 citation statements)
references
References 54 publications
38
256
6
4
Order By: Relevance
“…The relationship of diminished levels of Hsp90 protein in chondrocyte metabolism during OA has not been determined, but in another study, Hsp90 mRNA was diminished in OA compared with normal cartilage samples (9). Taken together, these findings suggest that decreased Hsp90 levels might play a role in ageassociated alterations in chondrocyte responses to external cues such as oxidative stress, which is an increasingly apparent contributor to older age-onset OA (38)(39)(40)(41)(42)(43)(44). Decreased levels of Hsp90 during aging may also contribute to altered growth factor responses and increased cellular senescence and therefore increased risk of older age-onset OA.…”
Section: Discussionmentioning
confidence: 98%
“…The relationship of diminished levels of Hsp90 protein in chondrocyte metabolism during OA has not been determined, but in another study, Hsp90 mRNA was diminished in OA compared with normal cartilage samples (9). Taken together, these findings suggest that decreased Hsp90 levels might play a role in ageassociated alterations in chondrocyte responses to external cues such as oxidative stress, which is an increasingly apparent contributor to older age-onset OA (38)(39)(40)(41)(42)(43)(44). Decreased levels of Hsp90 during aging may also contribute to altered growth factor responses and increased cellular senescence and therefore increased risk of older age-onset OA.…”
Section: Discussionmentioning
confidence: 98%
“…In these chondrocytes, the expression levels of type IX and type XI procollagens as well as link protein were higher than those in the cells given a control siRNA ( Figure 3C). In dedifferentiating chondrocytes, the expression levels of type I and type III procollagens, which are not very high in normal chondrocytes, have been shown to be induced in parallel with the decline in cartilage matrix gene expression (34)(35)(36)(37)(38). Thus, we expected that the expression of those procollagen genes might be reduced by the suppression of ␣v or ␤5 integrin expression.…”
Section: Determination Of Dominant Integrins In Human Articular Chondmentioning
confidence: 98%
“…During inflammation and/or oxidative stress, oxidative defense genes (i.e. SOD) are reported to be down-regulated in multiple tissues including astrocytes and chondrocytes (6,16,17). SOD has been discovered in three isoforms in humans.…”
Section: Discussionmentioning
confidence: 99%
“…Its main function is to protect cells and the ECM against the effects of superoxide anion (18). SOD2 has been shown to be down-regulated in OA while SOD3 is decreased in human OA and a mouse model of OA (16,22,23). Recently Scott et al found that all three SOD family members (SOD1, SOD2, and SOD3) were down regulated in diseased cartilage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation